Dietary determinants of obesity - Astrup, Arne (Henry Stewart Talks, 2007)
Environmental factors causing weight gain and obesity, Genes interacting with dietary fat, Portion size, Eating away from home, Recommended dietary composition of a weight-reducing diet, Risk of obesity and type 2 diabetes, Role of energy density, Fast food, Meta-analysis of low fat diets, Lifestyle intervention, Dietary composition, The Glycemic Index, Sugar-sweetened drinks and childhood obesity, Low carbohydrate vs. low fat diets, Hierarchy of satiety, Energy expenditure, Protein vs. carbohydrate, Dietary intervention